Precise molecular design for BN-modified polycyclic aromatic hydrocarbons toward mechanochromic materials. Issue 42 (14th September 2020) - Huang, Huanan; Zhou, Ying; Wang, Yawei; Cao, Xiaohua; Han, Chuan; Liu, Guochang; Xu, Zhixiong; Zhan, Changchao; Hu, Huanan; Peng, You; Yan, Ping; Cao, Dapeng
Abstract : This paper reports on a novel molecular-level design strategy to achieve a novel MCL material base on boron and nitrogen aromatics. The introduction of boron nitrogen unit is the key to design the MCL smart materials. Abstract : The development of smart materials, in particular those exhibiting highly sensitive mechanochromic luminescence (MCL) is desirable, but challenging since the MCL internal mechanism and the structure–performance relationship still remain unclear. Herein, we report a new MCL material, BN benzo[f]tetraphene, synthesized using a molecular-level design strategy by introducing a BN unit to a π-conjugated system. By investigating BN benzo[f]tetraphene (5 ) and its analogue, it was found that the introduction of the boron-nitrogen unit is the key to tailoring the molecular dipole moment and intermolecular interactions, which can therefore form an easily deformable molecular stacking pattern and endow 5 with wonderful MCL properties. Theoretical calculations confirmed that inherent energies like excited singlet (S) and highly sensitive triplet (T) states exist in the MCL process, and the formation and fracture of ordered molecular aggregates have significant effect on radiative and nonradiative transitions. The material also shows high-contrast and self-reversible properties related to thermal-and force-stimulus, which makes it a promising candidate for security ink, optical recording applications. This work possibly opens up a new way to develop efficient organic smart materials, and therefore, trigger the discovery of new functions and properties of azaborine compounds.